Transitional Cell Carcinoma within a Portion of Inguinally Herniated Bladder - Matthew A. Uhlman; Nathan A. Bockholt; Amit Gupta (Case Reports in Urology)
Bladder herniation within the inguinal canal is a relatively uncommon finding. We report an even less-common occurrence of transitional cell carcinoma located within a portion of inguinally herniated bladder. Fewer than 20 reports exist in the literature describing this scenario.